ANALISIS PENERAPAN PROJECT BASED LEARNING (PjBL) PADA PEMBELAJARAN IPAS SISWA KELAS 5 SEKOLAH DASAR - Atun Hasanah, Imra; Maria Zulfiati, Heri; Hasanah, Daimul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The aim of this research is to analyze the application of project based learning (PjBL) in science and science learning for grade 5 students at Muhammadiyah Parakan Elementary School. This research method uses qualitative methods. The subjects of this research were the 5th grade students of Hamzah SD Muhammadiyah Parakan, totaling 24 students. Of the 24 students, all of them were very interested and enthusiastic about the project based learning model. Data collection techniques in this research used interviews and observation. The data analysis technique used is qualitative descriptive data analysis. Project based learning is appropriate to apply, because students become more active and creative, confident, unified and supportive in giving their opinions and assessing other groups. This shows that project based learning is appropriate and successfully applied in class 5.